Phenotypic and genotypic characterization of influenza virus mutants selected with the sialidase fusion protein DAS181 - Triana-Baltzer, Gallen B. (Oxford University Press, 2011)
BACKGROUND: Influenza viruses (IFVs) frequently achieve resistance to antiviral drugs, necessitating the development of compounds with novel mechanisms of action. DAS181 (Fludase(®)), a sialidase fusion protein, may have a reduced potential for generating drug resistance due to its novel host-targeting mechanism of action. METHODS: IFV strains B/Maryland/1/59 and A/Victoria/3/75 (H3N2) were subjected to >30 passages under increasing selective pressure with DAS181. The DAS181-selected IFV isolates were characterized in vitro and in mice. RESULTS: Despite extensive passaging, DAS181-selected viruses exhibited a very low level of resistance to DAS181, which ranged between 3- and 18-fold increase in EC(50). DAS181-selected viruses displayed an attenuated phenotype in vitro, as exhibited by slower growth, smaller plaque size and increased particle to pfu ratios relative to wild-type virus. Further, the DAS181 resistance phenotype was unstable and was substantially reversed over time upon DAS181 withdrawal. In mice, the DAS181-selected viruses exhibited no greater virulence than their wild-type counterparts. Genotypic and phenotypic analysis of DAS181-selected viruses revealed mutations in the haemagglutinin (HA) and neuraminidase (NA) molecules and also changes in HA and NA function. CONCLUSIONS: Results indicate that resistance to DAS181 is minimal and unstable. The DAS181-selected IFV isolates exhibit reduced fitness in vitro, likely due to altered HA and NA functions.